If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11g + h = -5 Solving 11g + h = -5 Solving for variable 'g'. Move all terms containing g to the left, all other terms to the right. Add '-1h' to each side of the equation. 11g + h + -1h = -5 + -1h Combine like terms: h + -1h = 0 11g + 0 = -5 + -1h 11g = -5 + -1h Divide each side by '11'. g = -0.4545454545 + -0.09090909091h Simplifying g = -0.4545454545 + -0.09090909091h
| 4.22-0.14x=5x-2.205 | | -7x+3(x+4)=8 | | 23/9*3 | | -24+2m=-22 | | 7k^2-20=-10k | | 14/18=42/? | | -2(v-2)=-4v-4 | | 12+24=-36t | | 8m-5+2m= | | 7/9=c/18 | | 4n^2+3=-5 | | 2y+6+3y=-7+2 | | (X-4.95)/x | | 17/5*4 | | X^2-3Z=5 | | -6w+4(w-8)=-12 | | 4n^2-13=-9 | | (2+4p)(5)= | | 7y=4y+30 | | (3v)-(12)=15 | | 5y+8x+5=180 | | 4x^2-11=47 | | X^2+5x^2=53 | | 2/5=10/6 | | 8cos^3x-4cosx-4cos^2x+1=0 | | 2(4-4x)+1=2(1x+2)-5x | | 3c=126 | | e^3x+5=e^6 | | log(x-0.5)=log(x-1) | | X/2=156 | | 12+6w-4-h+2w+3s= | | 4/(x-3)=3/(2x)=y/21 |